Health research priorities in university theses in Puno, Peru - Mamani-Benito, Oscar (2021)
This research aimed to determine the frequency that national health research priority topics are addressed in university theses in Puno, Peru. This was an observational cross-sectional study conducted in 482 theses approved between 2016 and 2018 in universities’ schools of medicine (25.10 %), nursing (46.47 %), nutrition (18.46 %) and psychology (9.95 %) in Puno. A greater proportion of descriptive (56.84 %) and non-experimental research works (90.45 %) were found. The priority topics were mental health (7.05 %); human resources (6.22 %); malnutrition and anemia (18.87 %); maternal, perinatal and neonatal mortality (4.77 %); tuberculosis (1.86 %); cancer (5.80 %); high blood pressure, dyslipidemia and cardiovascular diseases (3.52 %); health policy and management (0.41 %); diabetes mellitus (7.46 %); and respiratory infections and pneumonia (5.60 %). Traffic accidents were not considered in this group. It is concluded that over 50 % of the theses from the universities in Puno address a health research priority topic.